1990
DOI: 10.1093/carcin/11.12.2133
|View full text |Cite
|
Sign up to set email alerts
|

Linear dose-response relationship for DNA adducts in rat liver from chronic exposure to aflatoxin B1

Abstract: Male F-344 rats were given [ 3 H]aflatoxin B, (AFBj) in the drinking water at three exposure levels (0.02, 0.6, 20 /*g/l, resulting in average dose levels of 2.2, 73, 2110 ng/kg per day). After 4, 6 and 8 weeks, DNA was isolated from the livers and analyzed for aflatoxin-DNA adducts. The level of DNA adducts did not increase significantly after 4 weeks, indicating that a steady-state for adduct formation and removal had nearly been reached. At 8 weeks, the adduct levels were 0.91, 32 and 850 nucleotide-aflatox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
33
2
1

Year Published

1994
1994
2011
2011

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(38 citation statements)
references
References 6 publications
2
33
2
1
Order By: Relevance
“…[37][38][39] Aflatoxin B1 was also found to be enzymatically activated in human hepatocytes and to bind to the third base of codon 249. 40,41 The expression of the 249 serine mutation was further shown to inhibit p53-dependent apoptosis and transcription and enhance liver cell growth in vitro. 42 This mutation was also found in nontumorous liver in correlation with aflatoxin B1 intake, 43 highlighting the notion that this mutation can occur early in the process of malignant transformation.…”
Section: Carcinogens and Tp53 Mutationsmentioning
confidence: 99%
“…[37][38][39] Aflatoxin B1 was also found to be enzymatically activated in human hepatocytes and to bind to the third base of codon 249. 40,41 The expression of the 249 serine mutation was further shown to inhibit p53-dependent apoptosis and transcription and enhance liver cell growth in vitro. 42 This mutation was also found in nontumorous liver in correlation with aflatoxin B1 intake, 43 highlighting the notion that this mutation can occur early in the process of malignant transformation.…”
Section: Carcinogens and Tp53 Mutationsmentioning
confidence: 99%
“…In addition to the direct mutagenicity of the metabolically activated AFB 1 to the 8, 9-epoxide that binds to DNA and forms the promutagenic N7dG adduct (Buss et al, 1990;Guengerich et al, 1996), AFB 1 can cause oxidative and nitrosative stress, and may indirectly induce TP53 249 ser mutations by lipid peroxidation ( Figure 4). Our recent studies indicate that oxidative-stress-generated 4-hydroxynonenal can induce TP53 249 ser mutations in vitro .…”
Section: Aflatoxin Bmentioning
confidence: 99%
“…In the livers of untreated animals the incidence of adenomas and carcinomas was 2.6%, and tumors increased linearly with concentration of 2-AAF in the diet, reaching 40% at the highest dose. In the bladder, by comparison, the tumor profile was nonlinear with a spontaneous rate of 0.3% that rose slowly to 2% at 75 ppm of dietary 2-AAF, and increased dramatically thereafter, resulting in incidences of 17 and 75% at doses of 100 and 150 ppm, respectively. A similar pattern of bladder hyperplasia preceded the bladder tumorigenesis in the EDOI study, which suggested that cell proliferation caused, or at least accompanied, the increase in tumorigenesis.…”
Section: Aromatic Aminesmentioning
confidence: 99%
“…A subsequent study by Buss et al (17) investigated hepatic DNA adduct formation by administering radiolabeled AFBI to male Fischer rats in the drinking water at doses of 0.02, 0.6, and 20 ppm for 8 weeks. The increase in DNA adduct formation was linear, with the highest DNA adduct level being 2.7 fmoles/jg DNA.…”
Section: Other Chemical Carcinogensmentioning
confidence: 99%